2008
DOI: 10.1016/j.crvi.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and biochemical changes during adventitious rooting of apple rootstocks MM 106 cultured in vitro

Abstract: Adventitious rooting in microcuttings of Malus rootstocks MM106 was studied as regards their histological and biochemical aspects. Microcuttings from shoots raised in Murashige and Skoog's (1962) medium were transferred into a rooting medium containing IBA in the dark, then fixed 0, 3, 5, 7 and 10 days after. Some cambial zone and adjacent phloem cells became dense cytoplasm, nuclei with prominent nucleoli and the first cell divisions were observed at day 3. Meristemoids became individualized, consisting of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 42 publications
5
73
0
2
Order By: Relevance
“…The next adventitious root initial formation and development of root primordia occurred in the expression phase simultaneously. Similar findings have been reported for microcuttings of Malus rootstock MM 106 (Naija et al, 2008) where initiation and development of adventitious roots were not synchronous and different stages of adventitious root development were observed at the same time in single pieces of stem.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The next adventitious root initial formation and development of root primordia occurred in the expression phase simultaneously. Similar findings have been reported for microcuttings of Malus rootstock MM 106 (Naija et al, 2008) where initiation and development of adventitious roots were not synchronous and different stages of adventitious root development were observed at the same time in single pieces of stem.…”
Section: Discussionsupporting
confidence: 77%
“…Peroxidase activity has been used to define rooting phases (induction, initiation and expression) (Gaspar et al, 1994) in several species: Elaeis guineensis (Rival et al, 1997), Psoralea corylifolia (Rout et al, 2000), Arbutus unedo and Taxus baccata (Metaxas et al, 2004), Ebenus cretica , Gardenia jasminoides (Hatzilazarou et al, 2006) and Malus rootstock MM 106 (Naija et al, 2008). In our work the pattern of change in peroxidase activity was similar in the stem bases and leaves of IBAleaf bud cuttings of elepidote rhododendron.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…, dehydrated consistent with [22]) and [23], via a graded n-butanol series and embedded in paraffin n wax. Sections of 8 -10 μm were cut and stained Safranin 0-fast green (FCF) for the general examination [24].…”
Section: Adventitious Roots Initiation and Development (Root Anatomy mentioning
confidence: 99%
“…Most woody plants require a sequence of two rooting media. Thus, Naija et al (2008) found that a period of 5 days in rooting medium with IBA was sufficient to induce 97% rooting in microcuttings of Malus × domestica Borkh. rootstock MM 106, and the exposure to IBA for periods longer than five days produced undesirable side effects on shoots, such as callus formation and leaf necrosis.…”
Section: Discussionmentioning
confidence: 99%